RESTITUTION FOR CHILD VICTIMS OF CRIME IN ACCORDANCE WITH THE PRINCIPLES OF PROPORTIONALITY AND THE BEST INTERESTS OF THE CHILD - I Nyoman Nurjaya; Ashifa Yona; Nurini Aprilianda (CV. RADJA PUBLIKA, 2025)
Children, as a vulnerable group, are frequently victims of crimes that may result in serious physical, psychological, and social impacts. One recognized recovery mechanism in Indonesian law is restitution. However, its implementation has not met ideal expectations. Using a socio-legal approach, this study aims to analyze the effectiveness of restitution for child victims, emphasizing the importance of the principles of proportionality and restorative justice. Two case studies reveal inconsistencies for example, a child involved in petty theft was sentenced to prison without adequate rehabilitative measures, while a victim of sexual violence received no restitution despite the perpetrator receiving a severe sentence. These findings reflect the reality that restitution remains a marginalized component of victim recovery, both structurally and normatively. Therefore, reforms in the juvenile criminal justice system are urgently needed, including simplifying procedures, strengthening relevant institutions, and establishing a compensation fund for victims. All these efforts aim to ensure that restitution is proportional, just, and genuinely aligned with the best interests of the child.